Study protocol for a randomized controlled trial: evaluating the effect of isokinetic eccentric training of the hamstring on knee function and walking function after total knee arthroplasty - Zhai, Tianjun; Song, Yongjia; Su, Jianqing; Wu, Ruiren; Wang, Jie; Zhang, Zengqiao; Feng, Wei (Frontiers in Medicine, 2024)
Introduction Total knee arthroplasty (TKA) is a widely-used treatment for end-stage knee osteoarthritis. However, it is common for patients to experience issues with knee joint function and abnormal gait following the surgery. Previous studies have primarily focused on concentric contraction of the quadriceps during TKA, neglecting the potential benefits of eccentric isokinetic training for the hamstrings. This protocol outlines a randomized, single-blind, controlled trial aimed at assessing the impact of eccentric isokinetic training for the hamstring muscles on pain, function, and gait in patients after TKA. Methods and analysis Fifty participants between the ages of 50 and 80 with knee osteoarthritis undergo unilateral total knee arthroplasty (TKA) for the first time. They will be transferred to the rehabilitation department 10–14 days after the operation. The participants are randomly divided into two groups, with 25 participants in each group: the control group and the Hamstring training group. The Control group will receive routine rehabilitation treatment, while the Hamstring training group will receive a combination of routine rehabilitation treatment and isokinetic eccentric training of the hamstring. The intervention will last four consecutive weeks. Both groups will be assessed at three different times: before the intervention, after 4 weeks of intervention, and 4 weeks after the interventions (follow-up). The primary outcome will be functional capacity (TUGT) and Hospital for Special knee Score (HSS). Secondary outcomes will be knee-related health status (isokinetic knee position perception, Peak torque of hamstring strength), pain intensity (Visual analog scale, VAS) and 3D gait analysis. Discussion The study aims to provide relevant evidence on the effectiveness of eccentric hamstring muscle contraction training in improving knee joint function and walking function after TKA. Clinical trial registration https://www.chictr.org.cn/showproj.html?proj=195544, Identifier ChiCTR2300073497.